Home is where the heart is - Byler, Linda (New York : Good Books, 2018)
Faced with adversity, Hannah grapples with her faith, struggling to understand who she is and where she belongs.
Keywords: Amish -- Fiction; Widows -- Fiction; Man-woman relationships -- Fiction; Romance fiction